Effect of aging and Varroa parasitism on the paracellular and transcellular permeability of the honeybee blood-brain barrier - Tyler Quigley; Gro Amdam (PLoS ONE, 2026)
Honeybees ( Apis mellifera ) provide crucial pollination services to agricultural systems globally, however, their healthspan in these contexts is constantly at risk. Agricultural environments impose a variety of sublethal stressors onto honeybees, including parasites, pathogens, pesticides, and poor nutrition. Synergies between age, age-associated tasks, and these stressors are believed to underlie colony failure trends of the past decade. Identifying the mechanisms by which age and stressors impact honeybee physiology is an important priority in protecting honeybee and other pollinator populations. An underexplored physiological structure in honeybees is the blood-brain barrier, a protective layer of cells that surrounds the brain. Here, we assess key dimensions of blood-brain barrier function; paracellular and transcellular permeability to molecules in the hemolymph. We measured these modes of permeability across worker groups that differ in age and foraging experience, as well as in bees exposed to varying levels of infestation by the parasitic mite Varroa destructor during development. Our results demonstrate that the paracellular permeability of the honeybee blood-brain barrier is stable across these age groups and upon Varroa exposure. In contrast, we found that transcellular permeability is increased in honeybees exposed to a high Varroa load. Together, these results demonstrate that age-related variation and parasitic stress differentially impact a primary protective structure of the honeybee central nervous system, which may lead to targeted interventions for protecting honeybee healthspan. The assay developed here may be easily applied to different aging- and stress-related contexts, further enabling studies focused on understanding maintenance and decline of the honeybee blood-brain barrier.